Thermal aging behaviors of the waste tire rubber used in bitumen modification. Issue 1 (February 2022) - Wang, Haopeng; Liu, Xueyan; Varveri, Aikaterini; Zhang, Hongzhi; Erkens, Sandra; Skarpas, Athanasios; Leng, Zhen
Considering the application scenarios of rubber granules from waste tires in the bitumen modification process (wet or dry process), both aerobic and anaerobic aging of rubber may occur. The current study aims to investigate the thermal aging behavior of waste tire rubber samples using nanoindentation and environment scanning electron microscopy (ESEM) tests. Both aerobic and anaerobic aging tests with different durations were conducted on rubber samples. The complex moduli of aged rubber samples were measured by nanoindentation tests. The surface morphology and elemental composition of aged samples were obtained by ESEM tests together with the energy dispersive X-ray analysis. Results have shown that for both aerobic and anaerobic aging, the equilibrium modulus derived from the complex modulus curve first increases and then decreases with aging time. However, the time needed for the aerobically aged sample to reach the maximum equilibrium modulus is shorter than the anaerobic case. Aging results in crack propagation and an increase of sulfur content on the rubber surface until it reaches the peak. The degree of crosslinking reflected by sulfur content for anaerobic aging is higher than aerobic aging. The morphological change and elemental change of rubber correlate well with the change of mechanical properties. The aging of rubber from the waste truck tire at 180°C can generally be separated into two stages: crosslinking dominant stage and chain scission dominant stage.